Factorial design to measure the effect of feeding biopreparations in pigs in the lifting stage (Business Vision, 2025)
The experimental design using the Completely Randomized Design (CRD) with a factorial arrangement is widely used to measure production factors in pig farms. The main objective was to measure the primary effects of essential oils and their concentration on response variables: weight, weight gain, food consumption, and feed conversion in piglets. The methodology employs a quantitative, experimental, and correlational approach. The sample consisted of 32 experimental units, distributed across four treatments with eight repetitions each. The results highlight a significant increase in weekly weight starting from week 5 with 2% oregano oil, although there were no statistical differences in weight gain. It concludes that essential oils, especially oregano at 2%, significantly influence food consumption and conversion, demonstrating the utility of factorial design in pig research.
Keywords: Production; food consumption; raw material; nutrient; food industry